2022
DOI: 10.1021/jacs.2c10595
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Separation of C8 Aromatic Isomers by Rationally Designed Nonaromatic Metal–Organic Frameworks

Abstract: The separation of C8 aromatics (xylenes and ethylbenzene) remains one of the most challenging industrial separations due to their similar structures and properties. Suitable adsorbents that can distinguish the small differences among isomers are urgently demanded. Herein, we demonstrate a strategy to realize the precise discrimination of C8 aromatics by constructing a nonaromatic confined pore environment with mixed polycycloalkane-type ligands. The nonaromatic low-polar pore environment avoids strong converge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In light of these findings, the MOF chemistry of tricarboxylate ligands is worthy of further study. On the other hand, although the aliphatic ligands endow the resulting frameworks with some unique properties, as shown in recent research work, , the aromatic-rich ones are still the most widely used, presumably because they are easier to synthesize or commercially available. Integrating more conjugated aromatic rings into organic linkers can not only significantly strengthen the structural rigidity and stability of the resulting materials but also furnish the affinity toward guest molecules based on specific π···π and C–H···π interactions .…”
Section: Introductionmentioning
confidence: 99%
“…In light of these findings, the MOF chemistry of tricarboxylate ligands is worthy of further study. On the other hand, although the aliphatic ligands endow the resulting frameworks with some unique properties, as shown in recent research work, , the aromatic-rich ones are still the most widely used, presumably because they are easier to synthesize or commercially available. Integrating more conjugated aromatic rings into organic linkers can not only significantly strengthen the structural rigidity and stability of the resulting materials but also furnish the affinity toward guest molecules based on specific π···π and C–H···π interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Structural Characterization. ZUL-C3 was successfully synthesized according to our previous report, 12 and ZUL-C4 was synthesized by heating the mixture of DMF/ethanol solution of Ni(NO 3 ) 2 •6H 2 O, H 2 bpdc, and ted at 413 K for 24 h for the first time. The experimental PXRD data revealed that ZUL-C4 was isostructural with ZUL-C3.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption separation offers less energy-extensive technical way by circumventing phase changes during the separation process. , Tremendous efforts have been devoted to the development of ultramicroporous adsorbents that can realize the efficient separation of C 2 H 4 /C 2 H 6 , and more than 600 adsorbents have been reported. Most of them showed an adsorption preference of C 2 H 4 from the C 2 H 4 /C 2 H 6 mixture due to the larger quadrupole moment (1.50 × 10 –26 esu cm 2 for C 2 H 4 ; 0.65 × 10 –26 esu cm 2 for C 2 H 6 ) and more π electrons of C 2 H 4 that enabled the stronger interactions between the C 2 H 4 molecule and the open metal sites or highly polar groups on the adsorbent pore surface. However, their similar molecular size tends to result in co-adsorption phenomenon, seriously reducing the product purity of C 2 H 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the gas separation mechanism, the effectiveness of ligand modification for optimizing performance has been well demonstrated. Among various functional groups, alkoxy groups exhibit outstanding availability. Compared to Lewis basic groups, alkoxy groups have the following advantages: (1) good hydrophobicity; (2) less impact on the structure because of weak coordination with metal ions and solvent molecules; and (3) chemical diversity in space resistance, flexibility, ability to provide electrons, and so on . What is more, alkoxy groups have a multi-directional impact on material performance, especially in improving separation selectivity: (1) splitting pores or channels, creating a more suitable pore size for the entry of guest molecules with a proper size; (2) as electron-donating groups, realizing the regulation of the pore polarity and influencing the host–guest interaction between the framework and gas molecules with high polarizabilities and quadrupole moment, thereby improving the gas selectivity; and (3) based on the flexibility, endowing MOFs with a distinctive “breathing” behavior or a “gate-opening” process, showing selectivity for specific gas molecules. Definitively, introducing alkoxy groups is helpful for improving gas selectivity.…”
Section: Introductionmentioning
confidence: 99%